О новых решениях задач по переходным процессам разряда конденсаторов - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
By using the new conception of transient processes, which is based on the expansion of jump-like signals in a series of components including the harmonic ones, the solutions of a number of problems concerning the discharge of capacitors are given.